Organization Training Needs Analysis for King Saud University - Saeed Nasser Saeed Alqahtani (Journal of Educational and Human Sciences, 2022)
King Saud University is the leading higher institution of learning in Saudi Arabia, which focuses on providing its students with the best quality of education. With more than 4600 staff members, the University provides educational and research activities with modern state of the art technology to give its students a rewarding experience. It caters to various audiences ranging from students, to professors, researchers of diverse fields, and non-academics. KSU also opens its doors to all types of students, whether local or international.